Indian spirituality : theory and praxis - Bhatt, S.R. (New Delhi Indian Council of Philosophical Research, 2018)
This is the first volume under ICPR's revived dissemination of knowledge series. It concisely talks about how to understand spirituality and its meaning in Indian context; the partnership of spirituality and science, and there by the need to make religion scientific and spiritualize science; nature and process of spiritual sadhna as it makes one an enlightened mind; bhakti yoga in Indian thought system; making devotion a household phenomenon and a social function; dharma as the overriding principle of Indian life and thought system; rajadharma as the Indian model of a welfare state that has a huge potential to have universal good etc.
Include Bibliography
Keywords: Philosophy -- Dharma -- Spirituality -- Yoga